A Myosin Va Mutant Mouse with Disruptions in Glutamate Synaptic Development and Mature Plasticity in Visual Cortex - Yoshii, Akira (Society for Neuroscience, 2013)
Myosin Va (MyoVa) mediates F-actin-based vesicular transport toward the plasma membrane and is found at neuronal postsynaptic densities (PSDs), but the role of MyoVa in synaptic development and function is largely unknown. Here, in studies using the dominant-negative MyoVa neurological mutant mouse Flailer, we find that MyoVa plays an essential role in activity-dependent delivery of PSD-95 and other critical PSD molecules to synapses and in endocytosis of AMPA-type glutamate receptors (AMPAR) in the dendrites of CNS neurons. MyoVa is known to carry a complex containing the major scaffolding proteins of the mature PSD, PSD-95, SAPAP1/GKAP, Shank, and Homer to dendritic spine synapses. In Flailer, neurons show abnormal dendritic shaft localization of PSD-95, stargazin, dynamin3, AMPARs and abnormal spine morphology. Flailer neurons also have abnormally high AMPAR miniature current frequencies and spontaneous AMPAR currents that are more frequent and larger than in wild-type while numbers of NMDAR containing synapses remain normal. The AMPAR abnormalities are consistent with a severely disrupted developmental regulation of long-term depression that we find in cortical Flailer neurons. Thus MyoVa plays a fundamentally important role both in localizing mature glutamate synapses to spines and in organizing the synapse for normal function. For this reason Flailer mice will be valuable in further dissecting the role of MyoVa in normal synaptic and circuit refinement and also in studies of neurological and neuropsychiatric diseases where disruptions of normal glutamate synapses are frequently observed.